Optimization of through-bolt steel beam connection to CFST column reinforced with rib plates using RSM method and MCEO algorithm - Khadijeh Ghanbari Soumeh; Hoseein Parvini Sani (Numerical Methods in Civil Engineering)
Today, one of the most important engineering requirements is to ensure optimal design with best possible seismic performance of structures. To this end, the present paper aims to apply the optimization process for the design of the through-bolt steel beam connection to the concrete-filled steel tube (CFST) column reinforced with rib plates. This study employs a multi-level cross-entropy optimizer (MCEO) algorithm along with response surface method (RSM) and finite element method (FEM) to establish the objective functions and constraints. The variables considered are the rib plate geometry and the steel and concrete strength parameters. In order to overcome problems, optimization is performed to increase the load-bearing capacity of the connection and to satisfy the constraints. Adopting this smart solution eliminates the need to connect finite elements for loop optimization and provides an explicit function for system performance. The results show that a very accurate analytical model can be developed to describe system performance using this process. This solution can optimize the performance of several systems that require a large amount of analysis and solve a wide range of structural optimization problems.